ASSISTING STUDENTS TO ATTACK WRITING TASKS ON IELTS TEST WITH â€œPROBING TECHNIQUEâ€ - Tedi Rohadi (English Review: Journal of English Education, 2015)
Abstract: Writing section on IELTS test is commonly considered one of the most difficult parts of test. The test takers can’t even understand what to do with the tasks provided. They eventually write without clearly knowing the expected direction. Therefore, there should be a fastest way to well equip students to successfully cope with such hindrances. This paper is an action research report of how to make students better understand and answer writing tasks on IELTS test by employing probing techniques as one of test taking strategies. The paper will preliminarily elaborate the characteristics or nature of IELTS test in general and writing section consisting two different tasks in particular including its indicators of what expected kind of writing the testees should be aware of. It will then discuss probing techniques in details. The attack strategies and their sequential implementation will afterward be discussed. The technique will assist students to respectively understand what and how to plan and write effectively on the test.Keywords: IELTS test, writing section, writing tasks, probing, attack strategies